An extensive examination of the influence of financial technology (Fintech) on advancing financial inclusion: a bibliometric investigation - Varun Kesavan; Aruna Polisetty (Discover Sustainability)
Abstract Financial technologies are the fundamental basis and driving force for financial inclusion initiatives, hence facilitating the attainment of the Sustainable Development Goals. This research is extensive and meticulous, focusing on the papers in the Scopus database related to fintech and financial inclusion. The data unequivocally demonstrate that China, India, and the United States are at the forefront of fintech and financial inclusion initiatives. Furthermore, the data reveals a significant increase in the number of articles pertaining to fintech and financial inclusion. The primary contributions in this field are Ozili PK, Banna H, and Zhang Y. Principal ties include Pan-Atlantic University, the University of Professional Studies, and Renmin University of China. This study indicates that successful fintech innovation enhances financial inclusion by bridging the divide between urban and rural communities, eventually contributing to sustainability. Likewise, effective financial innovation fosters increased growth in green investments, green initiatives, and green finance, transitioning economies from a linear to a circular model. The forthcoming research has the potential to enlighten and influence regulators, politicians, and future scholars.